Are the nutrient and textural properties of Australian commercial infant and toddler foods consistent with infant feeding advice?. Issue 7 (14th October 2020) - Moumin, Najma A.; Green, Tim J.; Golley, Rebecca K.; Netting, Merryn J.
Abstract: Infant feeding guidelines worldwide recommend first foods to be Fe rich with no added sugars and that nutrient-poor discretionary foods are to be avoided. Feeding guidelines also recommend exposing infants to a variety of foods and flavours with increasingly complex textures. Here, we compare nutritional and textural properties of commercial infant and toddler foods available in Australia with established infant feeding guidelines. Nutrition information and ingredient lists were obtained from food labels, manufacturer and/or retailer websites. In total, 414 foods were identified, comprising mostly mixed main dishes, fruit and vegetable first foods and snacks. Most products were poor sources of Fe, and 80 % of first foods were fruit-based. Half of all products were purées in squeeze pouches, and one-third of all products were discretionary foods. The nutritional content of many products was inconsistent with guidelines, being low in Fe, sweet, smooth in consistency or classified as discretionary. Reformulation of products is warranted to improve Fe content, particularly in mixed main dishes, expand the range of vegetable-only foods and textural variety. Greater regulatory oversight may be needed to better inform parents and caregivers. Frequent consumption of commercial baby foods low in Fe may increase the risk of Fe deficiency. Excessive consumption of purées via squeeze pouches may also have implications for overweight and obesity risk.